Activity Enhancement of G‐Quadruplex/Hemin DNAzyme by Flanking d(CCC). Issue 12 (27th January 2016) - Chang, Tianjun; Gong, Hongmei; Ding, Pi; Liu, Xiangjun; Li, Weiguo; Bing, Tao; Cao, Zehui; Shangguan, Dihua
Abstract: G‐quadruplex (G4)/hemin DNAzymes have been extensively applied in bioanalysis and molecular devices. However, their catalytic activity is still much lower than that of proteinous enzymes. The G4/hemin DNAzyme activity is correlated with the G4 conformations and the solution conditions. However, little is known about the effect of the flanking sequences on the activity, though they are important parts of G4s. Here, we report sequences containing d(CCC), flanked on both ends of the G4‐core sequences remarkably enhance their DNAzyme activity. By using circular dichroism and UV‐visible spectroscopy, the d(CCC) flanking sequences were demonstrated to improve the hemin binding affinity to G4s instead of increasing the parallel G4 formation, which might explain the enhanced DNAzyme activity. Meanwhile, the increased hemin binding ability promoted the degradation of hemin within the DNAzyme by H2 O2 . Furthermore, the DNAzyme with d(CCC) flanking sequences showed strong tolerance to pH value changes, which makes it more suitable for applications requiring wide pH conditions. The results highlight the influence of the flanking sequences on the DNAzyme activity and provide insightful information for the design of highly active DNAzymes. Abstract : G‐quadruplex/hemin DNAzymes : d(CCC)‐containing sequences flanking on parallel G‐quadruplexes improve the hemin binding affinity to G‐quadruplexes and result in the enhancement of the DNAzyme activity and hemin degradation, as well as increase the tolerance of DNAzymes to pH change (see figure).